1995
DOI: 10.1128/aac.39.4.941
|View full text |Cite
|
Sign up to set email alerts
|

Prophylaxis with enteral antibiotics in ventilated patients: selective decontamination or selective cross-infection?

Abstract: Selective decontamination of the digestive tract (SDD) has been evaluated as a method to prevent colonization and infection in ventilated patients in 40 trials. On the basis of an assumption that cross-infection would be reduced as a consequence of SDD and that this would distort the results of SDD studies that used concurrent controls, 14 studies used historic controls. To test this assumption, three observations from the two types of studies were compared. (i) The differences between observed and expected ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
1
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(59 citation statements)
references
References 60 publications
(89 reference statements)
5
52
1
1
Order By: Relevance
“…The gastropulmonary or rectopulmonary hypothesis (32) currently proposes that nosocomial pneumonia, especially ventilator-associated pneumonia (VAP), is caused by Gram-negative bacteria originating from the GI tract (33,34). In contrast, our findings provide evidence that the colonization of the two main K. oxytoca habitats (lower GI tract and respiratory tract) requires distinct genetic backgrounds.…”
Section: Discussioncontrasting
confidence: 53%
“…The gastropulmonary or rectopulmonary hypothesis (32) currently proposes that nosocomial pneumonia, especially ventilator-associated pneumonia (VAP), is caused by Gram-negative bacteria originating from the GI tract (33,34). In contrast, our findings provide evidence that the colonization of the two main K. oxytoca habitats (lower GI tract and respiratory tract) requires distinct genetic backgrounds.…”
Section: Discussioncontrasting
confidence: 53%
“…Selective digestive decontamination (SDD), an extensively studied method for VAP prevention (9,10), achieves decreased colonization with aerobic Gram-negative bacilli at the oropharynx (11) through the use of topical antibiotic paste. However, SDD may increase colonization with Gram-positive bacteria (12,13), including staphylococci (14,15).…”
mentioning
confidence: 99%
“…4 Since the Cochrane review, additional primary research has been published, which also showed a mortality benefit (OR 0.63; 95% CI 0.46 to 0.87). 5,6 However, a degree of controversy exists, with Hurley et al 7 challenging that, across these studies, the incidence of ventilator-associated pneumonia (VAP) at baseline was significantly lower in the ventilated control groups than in the SDD groups, which could falsely give the impression of benefit. 8 Nonetheless, if the documented mortality benefit could be realised in UK practice, then it could prevent as many as 2000-3000 avoidable deaths per annum.…”
Section: Fundingmentioning
confidence: 99%